2016
DOI: 10.1063/1.4963240
|View full text |Cite
|
Sign up to set email alerts
|

Parametric study of H-Darrieus vertical-axis turbines using CFD simulations

Abstract: A parametric study of vertical axis turbines of the H-Darrieus type is conducted using state-of-the-art Computational Fluid Dynamics (CFD) and the k-ω Shear Stress Transport RANS model in its unsteady form. Although most parameters have previously been investigated individually, the effect of solidity, number of blades, tip speed ratio, Reynolds number, fixed blade pitch angle, and blade thickness on the aerodynamic efficiency of the turbine is evaluated using the same performance evaluation set-up in order to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
54
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(60 citation statements)
references
References 20 publications
4
54
1
1
Order By: Relevance
“…The spatial and temporal resolutions of the simulations in this study have already been proven to be adequate in previous investigations on turbines [22,23,38]. Nonetheless, two more simulations for each turbine concept have been carried out in order to confirm the resolution adequacy.…”
Section: Numericsmentioning
confidence: 65%
See 1 more Smart Citation
“…The spatial and temporal resolutions of the simulations in this study have already been proven to be adequate in previous investigations on turbines [22,23,38]. Nonetheless, two more simulations for each turbine concept have been carried out in order to confirm the resolution adequacy.…”
Section: Numericsmentioning
confidence: 65%
“…The rotating shaft and connecting arms are not included in this study. More precisely, the CFT investigated corresponds to one of the single-bladed turbines studied by Gosselin et al [22], which is characterized by a NACA0015 profile, a blade's aspect ratio (b/c) of 15, a diameter to chord length ratio of 7 and a tip speed ratio of 4.25. As shown in Fig.…”
Section: Geometric Characteristics and Operating Parametersmentioning
confidence: 99%
“…In turn, Gosselin et al [25] performed a detailed 2D and 3D CFD analyses of a Darrieus wind turbine to study all the major factors affecting the turbine performance; i.e., TSR, Reynolds number, σ, N, AR, pitch angle (θ) and blade thickness. They also mentioned that for high-Reynolds applications, optimal radius-based σ is found to be around σ =0.2, while higher solidities show a lower maximum efficiency than what was previously published using simpler streamtube based methods [25].…”
Section: Introductionmentioning
confidence: 99%
“…According to Sabaeifard (2012), a 3-bladed Darrieus turbine with 35% solidity has the best efficiency among all geometries that were numerically studied in his work. 8 Gosselin (2013) simulated an H-type Darrieus wind turbine using the Fluent commercial code and found that the maximum power coefficient of turbine decreases when solidity increases. 9 Roh (2013), however, suggested that the maximum power coefficient increases with the increase of the solidity at first, beyond a certain solidity, the maximum power coefficient then decreases with further increasing solidity.…”
mentioning
confidence: 99%
“…8 Gosselin (2013) simulated an H-type Darrieus wind turbine using the Fluent commercial code and found that the maximum power coefficient of turbine decreases when solidity increases. 9 Roh (2013), however, suggested that the maximum power coefficient increases with the increase of the solidity at first, beyond a certain solidity, the maximum power coefficient then decreases with further increasing solidity. 10 Numerical analysis of blade-vortex interaction in a Darrieus wind turbine was conducted by Amet (2009), 11 but the effect of the observed physical phenomena on the aerodynamic performance of the Darrieus wind turbine was not explained in his work.…”
mentioning
confidence: 99%